A Comparative Study of Students’ Attitudes toward Mathematics in Southeast Asia: Evidence from Indonesia and Thailand - Kristayulita; Nur Hardiani; Alfira Mulya Astuti (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to explain students' attitudes toward mathematics in Southeast Asia, focusing on Indonesia and Thailand. Students' attitudes towards mathematics significantly influence their learning success and academic motivation. This quantitative study involved 494 secondary school students from Indonesia and Thailand. The instrument used was the Fennema-Sherman Mathematics Attitude Scales (F-SMAS) questionnaire with a two-way analysis of variance (ANOVA). The findings indicate that gender did not show substantial differences in Indonesia and Thailand at the secondary school level, but country of origin did. in Indonesia and Thailand at the secondary school level showed more positive attitudes towards mathematics than Thai students as seen from the higher average scores in self-confidence (Indo: 3.57, Thai: 3.11), greater maternal support (Indo: 3.67, Thai: 3.25), more optimistic perceptions about the usefulness of mathematics better preposition more optimistic perceptions of the usefulness of mathematics (Indo: 3.78, Thai: 3.39), and higher motivation (Indo: 3.32, Thai: 3.12). While there were no significant gender differences between the two countries, the stereotype of mathematics as a male domain was more pronounced in Indonesia (Indo: 3.55, Thai: 3.31), highlighting critical areas for intervention in the education system and the promotion of inclusive attitudes toward mathematics. These findings are expected to enhance the formulation of more contextual educational policies and encourage greater interest and achievement in mathematics among students in the Southeast Asian region.